Fruit Nutrients of Five Species of Wild Raspberries (Rubus spp.) from Indonesian Mountain’s Forests - Surya, Muhammad Imam; Suhartati, Siti; Ismaini, Lily; Lusini, Yuyun; Destri, Destri; Anggraeni, Dian; Normasiwi, Suluh; Asni, Nurul; Sidiq, Mirwan Abu Bakar (Journal of Tropical Life Science, 2018)
Rubus spp. (wild raspberries) is one of genera belongs to Rosaceae, also distributed in the mountain forest of Indonesia. It has a high potency to be cultivated plant. Although, some of the potential of Rubus has already known, information of about fruit nutrients of species that distribute in the mountain forest of Indonesia are not known yet. This study was aimed to determine the fruit nutrients of five species of wild raspberries that was collected in Cibodas Botanical Garden. The results of our experiments demonstrate that the fruits nutrients contents varied among five species of wild raspberries from Indonesian mountain's forests. Rubus fraxinifolius has the highest content of sugar (5.05 g sugar per 100 g fruits) compared to Rubus rosifolius, Rubus chrysophyllus, Rubus lineatus and raspberry. During the ripening and ripe period, there were a different value of vitamin C and iron contents. The highest vitamin C of R. fraxinifolius (83.65 mg/100 gram) on the ripening fruit stage II. On the other hand, the highest vitamin C of R. rosifolius (54.30 mg/100 gram) found on the stage of ripe fruit.